Design of a transportable miniaturized optical reference cavity with flexibly tunable thermal expansion properties - Zhao, Weinan; Wu, Hanxu; Fu, Yang; Ge, Jun; Yang, Honglei; Zhang, Shengkang (Frontiers in Physics, 2023)
A 3-cm-long optical reference cavity for transportable miniaturized ultra-stable laser is designed and analyzed by finite element analysis (FEA). Although the tiny cavity is formed in a conventional way, in which a cylinder spacer made of ultra-low expansion (ULE) glass is optically contacted with fused-silica mirror substrates and compensation rings, the compensation rings are specially designed in order to broaden the zero-thermal-expansion temperature tuning range. Besides, the cavity is capable to be rigidly fixed by clamping both end sections of the cylinder spacer along the axis transportation. The thermodynamic analysis shows that a larger tuning span of the zero-thermal-expansion temperature varying from -10 K to +23 K compared to all-ULE cavity is benefited, resulting in the whole optical reference cavity could work around room temperature. Meanwhile, the statics analysis indicates the design is insensitive to extrusion force and vibration, so that it owns a potential of solid performance after transportation.